Measurement of CP violation in B0→J/ψK0S - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; et al. (Physical review letters, 2015)
Measurements are presented of the CP violation observables S and C in the decays of B0 and ¯B0 mesons to the J/ψK0S final state. The data sample corresponds to an integrated luminosity of 3.0 fb−1 collected with the LHCb experiment in proton-proton collisions at center-of-mass energies of 7 and 8 TeV, and contains a total of 41 560 selected B0 and ¯B0 decays. The analysis of the time evolution of these decays yields S=0.731±0.035(stat)±0.020(syst) and C=−0.038±0.032(stat)±0.005(syst). In the standard model, S equals sin(2β) to a good level of precision. The values are consistent with the current world averages and with the standard model expectations.